The Quest to Restore NAALSABHA in Lamjung: Tamu Peoples’ Customary Governance System - Ghale, Khim (Indigenous Nationalities Studies आदिवासी जनजाति अध्ययन, 2025)
The NAALSABHA, historically a pivotal self-governance institution for the Tamu (Gurung) community, played a crucial role in cultural cohesion, natural resource management, customary rule-making, and mediating relations with the state. However, state interventions led to its decline. Despite this, its memory has been preserved through oral traditions, and recent efforts within the community aim to revive this institution. This article examines the emergence, functions, decline, and restoration attempts of the NAALSABHA through the frameworks of Indigenous self-governance, decolonization, and revitalization. The NAALSABHA, with successful revival contingent upon sustained community mobilization, advocacy for legal recognition, and strategic leadership.